Acute effect of coffee on aortic stiffness and wave reflections in healthy individuals: differential effect according to habitual consumption. (3rd October 2018) - Ioakeimidis, Nikolaos; Tzifos, Vaios; Vlachopoulos, Charalambos; Terentes-Printzios, Dimitrios; Georgakopoulos, Christos; Tousoulis, Dimitrios
Abstract: The acute effect of coffee on arterial stiffness and its dependence on habitual consumption was studied in 24 volunteers on four separate occasions during which subjects received: (a) coffee espresso, (b) decaffeinated coffee espresso, (c) caffeine alone and (d) placebo (hot water). The increase in carotid femoral pulse wave velocity (PWV), augmentation index (AIx) and augmented pressure (AP) of the aortic pressure waveform after coffee consumption was more pronounced in non-habitual ( n  = 13) compared to habitual drinkers ( n  = 11), (differences of maximal changes between groups in PWV, AIx, AP responses by 0.39 m/s, 4.5% and 1.9 mmHg, respectively, for coffee; and by 0.34 m/s, 5.3% and 2.1 mmHg, respectively, for decaffeinated coffee; all p  < .05). Caffeine increased PWV, as well as AIx and AP but differences in responses between the two groups were not significant. Both caffeinated and decaffeinated coffee consumption is associated with a more potent effect on arterial stiffness in non-habitual than habitual coffee consumers, whereas caffeine induces comparable changes in both groups.